Monitoring and Supervision Management of Islamic Education, Deep Learning and AI, Local Wisdom Concept, Love-Based Curriculum in Elementary Madrasahs - Nursyahbani Chusnul Novita; Novia Nurhayati; Al Aliefa Turrasyid; Ahmad Zainuri (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines the monitoring system in the management of Islamic education supervision at Madrasah Ibtidaiyah through the utilization of Deep Learning and Artificial Intelligence (AI) technologies, integrated with local wisdom values and the implementation of a love-based curriculum. Supervision in Islamic education is viewed as a strategic element in maintaining the quality of the learning process while simultaneously fostering students’ character development in a holistic manner (Sergiovanni, 2019). The research adopts a qualitative approach using a library research method. The findings indicate that the application of AI in supervision enhances the effectiveness of monitoring processes, improves the accuracy of teacher performance evaluation, and supports continuous mapping of students’ learning development without neglecting spiritual, humanistic, and local cultural values.